Analyzing the Impact on Teacher Preparedness as a Result of Using Mursion as a Risk-free Microteaching Experience for Pre-service Teachers. (June 2022) - Ferguson, Sarah; Sutphin, Latanya
Risk-free micro-teaching affords an opportunity for pre-service teachers (PTs) to practice teaching and student engagement techniques outside of a traditional classroom setting. More time to practice teaching is often an expressed desire of PTs. Orchestrating time to practice teaching techniques learned in pedagogy courses is a difficult undertaking for teacher educators, especially while trying to ensure low-risk or risk-free experiences. As explained through this study, the implementation of a Mursion simulation to offer risk-free micro-teaching experiences for PTs served as a valuable addition to an introductory teaching course. The Mursion experience enhanced PTs' personal preparation for teaching as well as enhancing their professionalism and lesson quality.